VARK Learning Styles and Their Relationship to Learning Outcomes in an Instructional Media Course - Indriyani, Feni; Nurmasitah, Sita (Universitas Negeri Semarang, 2025)
This study investigates the relationship between VARK learning styles (Visual, Auditory, Read/Write, and Kinesthetic) and student learning outcomes in the Instructional Media course within the Home Economics Education Program at the Faculty of Engineering, Universitas Negeri Semarang. Understanding diverse learning styles is essential to supporting effective instruction; however, mismatches between students’ preferences and teaching approaches are frequently observed. A quantitative survey design was employed, in which students’ learning styles were identified using the VARK questionnaire, while final course grades were obtained through academic records. Data were analyzed using the Spearman rank correlation and the Kruskal-Wallis test. The results indicated no statistically significant correlation between learning styles and learning outcomes (ρ = 0.018; p = 0.916), and no significant differences in outcomes across learning style groups (H = 1.585; p = 0.663). Despite the lack of statistical significance, descriptive analysis revealed that students with multimodal learning preferences tended to achieve higher average scores than their unimodal peers. These findings suggest the pedagogical value of accommodating diverse learning styles, particularly through flexible and multimodal instructional strategies.